PENGGUNAAN LKPD MODEL IDEAL PROBLEM SOLVING UNTUK MENINGKATKAN KOMPETENSI FISIKA PESERTA DIDIK - Nurhafifah Nurhafifah; Hidayati Hidayati; Zulhendri Kamus (PILLAR OF PHYSICS EDUCATION, 2018)
The achievement of students physics competence is not yet satisfy expetation. There are several factors to effect this problem such as the teacher centered learning, teaching materials that still have not varied, and students have not been involved learning in the process to find knowledge. The purpose of research is to determine the effect of implementation LKPD with IDEAL problem solving model in spring elasticity and static fluid to the physics competence of students grade XI SMAN 5 Padang. The type of research is pre-experimental design with one shoot case study research design. Populations in this research are all students of grade XI SMAN 5 Padang in academic year 2017/2018. Sampling tecnique use purposive sampling. The research data are values of attitude, knowledge, skill in laboratory, and LKPD with IDEAL problem solving model. Data of attitude competence is analyzed using descriptive  statistic. Data of knowledge and skill competence are analyzed using simple linear regression and correlation analysis at significant level 0,05. The correlation analysis of LKPD with IDEAL problem solving model to students competence obtained in the amount of 45,46% for knowledge and 51,84% for skill compatence. Based on analysis found that there is significant effect on implementation LKPD with IDEAL problem solving model in spring elasticity and static fluid to physics competence of students grade XI SMAN 5 Padang.